FRI0043 Peptides highly specific to the variable region of TNF-ALFA-specific references licensed (RL) monoclonal antibodies (MAB), as potential tool to effectively assess similarity between biosimilars and the correspondig RL MAB. (15th June 2017) - Favoino, E; Ionescu, C; Perosa, F
Abstract : Background: Monoclonal antibodies (mAb) have greatly facilitated the development of highly specific immunotherapy, with a significant improvement of clinical outcome in certain rheumatologic diseases. However, the approaching of many references licensed mAb (RLM) to the end of their licensing period, have stimulated a tremendous interest in the synthesis of a new generation of low-cost mAb referred to as biosimilars (BS) mAb (BSM), because of their similarity to the RLM. An essential requirement imposed by Regulatory Agencies for a mAb to be considered BS is that its variable region (VR) primary sequence must be highly similar to that of RLM. However, epitope recognition and affinity of a mAb very much depends on its VR conformational structure, which may differ even between two mAb bearing highly similar (but not identical) VR. The availability of reagents highly specific to the RLM VR may offer an unique opportunity to define whether a mAb can or cannot be considered BS to a given RLM. Objectives: To isolate and characterize phage clone-expressing peptide (pc) which are highly specific for the VR of two anti-TNF-α RLP namely mAb Infliximab (Inf) and Golimumab (Gol). Methods: Cross-inhibition ELISA on recombinant TNF-α (rTNF-α) was performed to define the spatial relationship among the epitopes detected by mAb. mAb-specific phage clones expressing peptide (pc) were obtained by the panning of a phage peptide display library with TNF-a specific mAb. Characterization of pc-specificity and of the spatial relationship between pc- and the TNF-a-binding site on the variable region of mAb was assessed by binding and inhibition assay. Results: mAb Inf and Gol specifically and dose-dependently cross-inhibited each to the other in the binding to rTNF-a, indicating the recognition by these 2 mAb of the same or two distinct spatially related epitopes on TNF-a. The panning of mAb Inf and Gol with a phage peptide display library resulted in the isolation of one Inf-specific pc (pcInf) and three Gol-specific pc (pcGol1 to 3). Binding assay showed that pcInf and the three pcGol specifically reacted with the corresponding mAb. Furthermore, pcInf and pcGol3 specifically and dose-dependently inhibited the binding of the corresponding mAb to rTNF-α, suggesting the recognition by the pc of the corresponding mAb antigen-combining site. Finally, pcInf and all three pcGol did not react with two additional TNF-a antagonists, suggesting that they are highly specific for mAb Inf and Gol respectively. Conclusions: The highly specificity of the pc described indicates that they can be eventually employed to predict similarity between a newly synthesized BSM and the claimed RLM, based on the BSM reactivity (or the lack of reactivity) with RLM-specific pc. Disclosure of Interest: None declared